(untitled) (Web of Teachers: Inderscience Research, 2023)
Alumina-based catalysts are mainly used in petrochemistry and oil refining for hydrotreating, reforming, cracking, and isomerization processes (73%). The share of aluminium oxide for drying gases and air is 17%. Sulfur catalysts, acid gas adsorbents and other sorbents account for 10%. The market for catalysts and sorbents based on aluminum oxide is specific: manufacturers work to order, and prices are formed individually.